Lehr-Lernforschung und Professionalisierung Perspektiven der Berufsbildungsforschung - Faßhauer, Uwe; Aff, Josef; Fürstenau, Bärbel; Wuttke, Eveline (Schriftenreihe der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2011)
Vocational training research The main topics of teaching-learning research and professionalisation are analysed both empirically and theoretically from the perspective of current research projects. The focus is on the effectiveness of specific teaching methods and support measures as well as on the professional skills of training personnel.